Development of a new method of crack modeling and prediction algorithm - Aibinu, Abiodun Musa; Shafie, Amir Akramin; Salami, Momoh Jimoh Emiyoka; Salami, Abdulazeez F.; Bamgbopa, I. A.; Lawal, Wahab Adetunji (2008)
In this report, the well known parametric method of signals and systems representation is extended to modeling and prediction of cracks on building and road surfaces. Also, a new algorithm based on complex value autoregressive neural network with split linear activation function for the determination of Complex-Value Autoregressive Moving average (CARMA) coefficients is also proposed in this report. Furthermore, mathematical derivation and detail analysis of the proposed CARMA based Complex-Value Neural Network (CVNN) algorithm is also discussed in this work.